The Effectiveness Of Internal Governance In Controlling Tax Risk - Haqi Fadillah; Khomsiyah Khomsiyah; Murtanto Murtanto (Institut Bisnis dan Informatika Kesatuan, 2026)
Main Purpose – This study examine the effectiveness of Internal Governance, which includes Board Risk Oversight, Corporate Governance, and Internal Control Quality, in controlling Tax Risk, with Internal Information Quality as a moderating variable. Method – The analysis employs panel data regression, moderated regression analysis (MRA), and Robustness Test using 230 observations from 46 Financial Sector companies listed on the Indonesia Stock Exchange for the 2020-2024 period. Main Findings – The results show that Risk Oversight and Corporate Governance effectively control Tax Risk, while Internal Control Quality does not show significant effectiveness. Internal Information Quality also does not moderate the relationship among the main variables. Theory and Practiccal Implications – The findings strengthen Agency Theory and emphasize the importance of supervisory coordination to enhance tax compliance, while providing insights for regulators and financial institutions to reinforce internal governance. Novelty – This study develops a Board Risk Oversight model by adding three effectiveness dimensions, Board of Commissioners, Audit Committe, and Risk Monitoring Committe, which improve the model’s explanatory power for variations in Tax Risk. Keywords: Board Risk Oversight; Corporate Governance; Internal Control Quality; Internal Information Quality; Tax Risk